World of chemistry - Young, Robyn V. 1958-.; Sessine, Suzanne 1976-. (Detroit Gale Group, 2000)
Articles on theories, discoveries, concepts, and notable people in chemistry.
Includes bibliographical references and indexes.
Keywords: Chemistry; Chemistry -- Encyclopedias